Pengaruh Hasil Belajar dan Soft Skills terhadap Kesiapan Kerja Siswa - Khamsiina Aufi; Agus Irianto (Jurnal Ecogen, 2023)
This research purposes to identify and analysis the learning outcomes and soft skills on work readiness effect of 12th grade students of state vocational high school at the marketing expertise program in Padang for the academic year 2019/2020. The research population were 104 students of class 12th marketing expertise program in Padang for the academic year 2019/2020. The technique for data analysis used is analysis by path. The research  results  show that 1) Soft skills have a  effect in positive and significant on learning outcomes of 12th state vocational high school  grade students of marketing expertise program in Padang for the 2019/2020 academic year, 2) Learning outcomes have a  effect  in positive and significant on the work readiness of 12th grade students of state vocational high school of marketing expertise program in Padang for the 2019/2020 academic year, and 3) Soft skills have a  effect  in positive contribution and significant on work readiness of 12th grade students of state vocational high school of marketing expertise program in Padang for the academic year 2019/2020.